2018
DOI: 10.9775/kvfd.2018.19754
|View full text |Cite
|
Sign up to set email alerts
|

Tavuk Karkaslarından İzole Edilen Salmonella spp. ve Listeria monocytogenes Prevalansı, Antimikrobiyal Direnci ve Moleküler Karakterizasyonu

Abstract: How to Cite This ArticleBasaran Kahraman B, Issa G, Kahraman T: Prevalence, antimicrobial resistance and molecular characterization of Salmonella spp. and Listeria monocytogenes isolated from chicken carcass . Kafkas Univ Vet Fak Derg, 24 (5): 775-779, 2018775-779, . DOI: 10.9775/kvfd.2018 AbstractThis study aimed to investigate the prevalence of Salmonella spp. and Listeria monocytogenes, their antimicrobial resistance profile. L. monocytogenes was not isolated from any of the samples. Salmonella spp. was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…On the other hand, many others reported the presence of L. monocytogenes in proportions similar to the findings of our study, like Bailey et al [22] in 23% of 90 chicken carcasses; Rorvik et al [23] in 20% to 100% of chicken carcasses from 5 slaughterhouses. In literature review, some of the studies that reported the presence of L. monocytogenes at lower values than the results of our study were as follows: Alsheikh et al [24] , 13.6% of the 250 ready-made chicken products; Alsheikh et al [25] , 12.8% of the 500 frozen chicken samples; Genigeorgis et al [26] 12.5% of 160 chicken meats; Zeinali et al [27] 18% of 200 fresh chicken carcasses; Basaran Kahraman et al [28] 0% of 400 chicken carcasses. Although there were no studies on the presence of L. monocytogenes in organic poultry in Turkey, a limited number of studies are available in the literature.…”
Section: Discussionsupporting
confidence: 43%
“…On the other hand, many others reported the presence of L. monocytogenes in proportions similar to the findings of our study, like Bailey et al [22] in 23% of 90 chicken carcasses; Rorvik et al [23] in 20% to 100% of chicken carcasses from 5 slaughterhouses. In literature review, some of the studies that reported the presence of L. monocytogenes at lower values than the results of our study were as follows: Alsheikh et al [24] , 13.6% of the 250 ready-made chicken products; Alsheikh et al [25] , 12.8% of the 500 frozen chicken samples; Genigeorgis et al [26] 12.5% of 160 chicken meats; Zeinali et al [27] 18% of 200 fresh chicken carcasses; Basaran Kahraman et al [28] 0% of 400 chicken carcasses. Although there were no studies on the presence of L. monocytogenes in organic poultry in Turkey, a limited number of studies are available in the literature.…”
Section: Discussionsupporting
confidence: 43%